Respuestas

  • Usuario de Brainly
2013-03-06T22:44:14+01:00

Datos :                         Fórmula : an = a1*(r)^(n-1)

r = 1/2                                              a7  = a1 *(1/2)^(7-1)

a7 =  1/64                                       (1/64) =  a1 *(1/2)^(6)

n = 7                                                (1/64) = a1*(1/64)

a1 = ?                                              (1/64) : (1/64) = a1

                                                  Multiplicamos CruzaDo :

                                                            64/64 = a1

                                                                   1 = a1

  Rpta/ El primer término de nuestra Progresión Geométrica es "1".

                         Un SaLuDo :)'